Policy review of the implementation of Fisheries and Aquatic Resources Management Council (FARMCS) in Region 6 - Delos Santos, Wilfredo D. (University of the Philippines in the Visayas, 2001)
The FARMC was created to ensure active and extensive participation of fisherfolk in the management and control over fisheries and aquatic resources. This concept, long advocated by the fisherfolk, gives due recognition and meaningful participation in the management of the fisheries aquatic resources in their respective areas of jurisdiction. The formation of FARMC as an institutional arrangement and management tool available to decision-makers showed promising results. There are several factors that hinder the formation of FARMCs and to attain its objectives. These problems and constraints include: lack of budget, lack of institutional capacity building training, fisherfolk are not interested to organize, and lack of LGU support. The study recommends to review and amend the conflicting provisions of RA 8550 and RA 7160, spell out the holes of national agencies mandated to render technical assistance to FARMC to avoid overlapping of function and misinterpretation of the provision of FAO 196 and strengthen the existing FARMCs in terms of capacity building trainings and managerial skills.